The natural history of multiple sclerosis: a geographically based study. 6. Applications to planning and interpretation of clinical therapeutic trials in primary progressive multiple sclerosis. - Cottrell, D; Kremenchutzky, M; Rice, G; Hader, W; Baskerville, J; Ebers, G (1999)
The natural history of primary progressive multiple sclerosis (PP-multiple sclerosis) recently has been defined in a geographically based multiple sclerosis population. For a series of prognostically defined hypothetical entry criteria based upon current trends in presentation to the London Multiple Sclerosis Clinic, we determined the number of patients who would have been trial eligible. Using 23 year mean longitudinal natural history data, we identified the observed rate of deterioration for frequently used trial endpoints. Hypothetical entry criteria were based on the practical considerations which would attend the execution of clinical trials in progressive multiple sclerosis. We then developed a series of sample size tables giving the number of patients with PP-multiple sclerosis and the length of observation that would be required to detect a significant result (P = 0.05) for a 25, 50 and 75% decrease in the median time to progression with 80 or 90% power, with treatment efficacy based upon the ability to slow progression on the disability status score. It is expected that the considerations outlined here will prove useful for both trial design and interpretation of trials in PP-multiple sclerosis which will require multi-centre collaborative efforts.